Perlindungan Hukum Dalam Pelaksanaan Bisnis Asuransi Sebagai Bentuk Investasi Berdasarkan Hukum Positif Indonesia - Kevin Burjuan Adisatya Sirait; Rani Apriani (Jurnal Ilmiah Wahana Pendidikan, 2022)
Investment is an economic activity between business actors and consumers to achieve a certain goal, regulated in Law No. 25 of 2007 concerning Investment, all forms of investment for business activities are regulated in this law. Investment is widely seen as an economic activity that is oriented towards economic progress and development in the country it self. Especially in Indonesia. An interesting investment is insurance, because its existence and existence can be seen from the regulation of laws and regulations in Indonesia which has existed since 1992 with the legitimacy of Law no. 40 of 2014 concerning Jo's Insurance. Law No. 2 of 1992 concerning Insurance Business. Of course this makes consumers and prospective consumers as parties who bind themselves with insurance companies are required to be competent and aware in carrying out these investment activities. Therefore, with the prevailing laws and regulations as an effort to protect the law so that the investment business climate is expected to be a glimmer of hope in maintaining the stability of investment business activities, especially in the insurance sector.